Cerebral and Brainstem Electrophysiologic Activity During Euthanasia with Pentobarbital Sodium in Horses. (19th March 2015) - Aleman, M.; Williams, D.C.; Guedes, A.; Madigan, J.E.
Abstract : Background: An overdose of pentobarbital sodium administered IV is the most commonly used method of euthanasia in veterinary medicine. Determining death after the infusion relies on the observation of physical variables. However, it is unknown when cortical electrical activity and brainstem function are lost in a sequence of events before death. Hypothesis/Objectives: To examine changes in the electrical activity of the cerebral cortex and brainstem during an overdose of pentobarbital sodium solution for euthanasia. Our testing hypothesis is that isoelectric pattern of the brain in support of brain death occurs before absence of electrocardiogram (ECG) activity. Animals: Fifteen horses requiring euthanasia. Methods: Prospective observational study. Horses with neurologic, orthopedic, and cardiac illnesses were selected and instrumented for recording of electroencephalogram, electrooculogram, brainstem auditory evoked response (BAER), and ECG. Physical and neurologic (brainstem reflexes) variables were monitored. Results: Loss of cortical electrical activity occurred during or within 52 seconds after the infusion of euthanasia solution. Cessation of brainstem function as evidenced by a lack of brainstem reflexes and disappearance of the BAER happened subsequently. Despite undetectable heart sounds, palpable arterial pulse, and mean arterial pressure, recordable ECG was the last variable to be lost after the infusion (5.5–16 minutes after end of the infusion). Conclusions and Clinical Importance: Overdose of pentobarbital sodium solution administered IV is an effective, fast, and humane method of euthanasia. Brain death occurs within 73–261 seconds of the infusion. Although absence of ECG activity takes longer to occur, brain death has already occurred.